Teaching in higher education requires applying strategies of achievement by teachers, in the search of the continuous knowledge of the pupil - Rivera León, Félix Armando (2018)
The present investigation is oriented to look for strategies that generally contribute to the quality in the results of the teaching work, whose responsibility is to contribute with the continuous knowledge of the students that are formed in Higher Education.In the same way it affects the efficiency in the teaching work as well as the encouragement, inculcate, and defend the development of the student's criteria; to emphasize that educational institutions, such as the central government must be obliged to establish norms and policies, and others that demand responsibility, innovation in teachers of Higher Education.